Amazonic context and the training of field teachers in Amazonas - Heloisa da Silva Borges; Claudio Gomes da Victoria; Helena Borges da Silva; Érica de Souza e Souza (Universidade Federal do Norte do Tocantins, 2022)
The Amazon context expressed in this text results from the experience of teacher training actions of the Escola da Terra Program, in 46 municipalities in the State of Amazonas, through the Faculty of Education, of the Federal University of Amazonas, which offered the Course of Improvement in Rural Education - Pedagogical Practices. Escola da Terra is an action of the former Department of Continuing Education, Literacy, Diversity and Inclusion (SECADI/MEC), in partnership with Higher Education Institutions, with State and Municipal Education Departments. In this way, it was possible to provide continuing education to teachers who work in multi-grade schools in the Amazonian countryside. The objective of the study was to socialize this experience of continuing teacher education developed by the Faculty of Education/UFAM, whose work has been developed for more than five years in the form of an action research methodological approach. As a result, we found out that 2,724 teachers from the interior of the State were assisted, who developed works with a focus on the formative times of alternation, associating teaching with research. As for the final considerations of the study, it is possible to say that the actions are important for the training of teachers of the multigrade classes of rural schools in Amazonas, since they strengthen the culture of Amazonian rural subjects.